Refractive errors in age group seven to fifteen years: North-east India scenario - Hazarika, Himanto Nath; Bhuyan, Dipak; Hazarika, Suranjana Chaliha; Addya, Sujit (International Journal Of Community Medicine And Public Health, 2017)
Background: The objectives of study were to find out the different types of refractive errors in children between seven to fifteen years age group and the cause of uncorrected defective vision. Methods: A prospective study was designed of two thousand children aged between seven to fifteen years, attending outpatient department. Study period was one year. Consent was obtained from their guardian. Inclusion criteria were children with refractive errors. Children presenting with organic defects of ocular structures, infections, corneal opacity, cataract, choroid and retinal disorders were excluded from study. Data were collected by history taking and comprehensive ocular examination, visual tests for both near and distant vision. Refractive error assessed by cycloplegic drug with one percent Homatropine eye drops, by streak retinoscopy. Objective refraction were carried out and documented. Subjective refraction was done after one week. Both BCVA and uncorrected refractive errors were ascertained and recorded. Results: Out of two thousand children examined, myopic = 34%, hypermetropic = 11%, and astigmatic = 55%. M: F = 900:1000. Study showed headache as the commonest symptom. 17% of the patients had positive family history. Correctable errors constitute 91% of the total cases. Conclusions: Myopic astigmatism was found to be the most frequent refractive error in children. Mass screening is required for early diagnosis of refractive error. Prescribing corrective glasses for children with refractive errors at an early age will prevent childhood morbidity.